STUDYING REACTIVITY RATIOS AND PHYSICAL PROPERTIES OF METHACRYLIC ACID - ETHYL ACRYLATE COPOLYMER - Thang, Tran Vu; Ha, Pham Thi Thu; Khoi, Nguyen Van; Manh, Nguyen Van; Trang, Pham Thi Thu (Vietnam Journal of Science and Technology, 2015)
The copolymerization of methacrylic acid (MAA) and ethyl acrylate (EA) was performed by free radical polymerization in ethanol, in the presence of 2,2-azobisisobutyronitrile (AIBN) as an initiator. The reactivity ratios of monomers were caculatured by Kelen-Tudos method using data from elemental analysis. The charaterstics of the copolymes were studied by IR spectroscopy, DSC, gel permeation chromatography (GPC) and TGA analysis methods. The results showed that MAA has higher reactivity than EA (rMAA = 2.63 and rEA = 0.21), glass transiton temperature of copolyme Tg = 146 oC, the average molecular weight of the copolymers Mw = 251000 (u) and the polydispersity index (PDI) Mw/Mn = 1.70.